Elucidation of iron homeostasis in Acanthamoeba castellanii. Issue 8 (July 2022) - Grechnikova, Maria; Arbon, Dominik; Ženíšková, Kateřina; Malych, Ronald; Mach, Jan; Krejbichová, Lucie; Šimáčková, Aneta; Sutak, Robert
Graphical abstract: Highlights: Acanthamoeba castellanii employs ferric reductase and the divalent iron transporter for iron assimilation. Expression levels of these proteins are significantly higher under iron limitation. Both proteins are localized to the membranes of acidified digestive vacuoles. Iron uptake is induced under iron depletion while the pinocytosis rate is reduced. Excessive iron is removed from the cytosol into the vacuoles by the VIT family protein. Abstract: Acanthamoeba castellanii is a ubiquitously distributed amoeba that can be found in soil, dust, natural and tap water, air conditioners, hospitals, contact lenses and other environments. It is an amphizoic organism that can cause granulomatous amoebic encephalitis, an infrequent fatal disease of the central nervous system, and amoebic keratitis, a severe corneal infection that can lead to blindness. These diseases are extremely hard to treat; therefore, a more comprehensive understanding of this pathogen's metabolism is essential for revealing potential therapeutic targets. To propagate successfully in human tissues, the parasites must resist the iron depletion caused by nutritional immunity. The aim of our study is to elucidate the mechanisms underlying iron homeostasis in A . castellanii . Using a comparative whole-cell proteomic analysis of cells grown under different degrees of iron availability, we identified the primary proteins involved in Acanthamoeba iron acquisition. Our results suggest a two-step reductive mechanism of iron acquisition by a ferric reductase from the STEAP family and a divalent metal transporter from the NRAMP family. Both proteins are localized to the membranes of acidified digestive vacuoles where endocytosed medium and bacteria are trafficked. The expression levels of these proteins are significantly higher under iron-limited conditions, which allows Acanthamoeba to increase the efficiency of iron uptake despite the observed reduced pinocytosis rate. We propose that excessive iron gained while grown under iron-rich conditions is removed from the cytosol into the vacuoles by an iron transporter homologous to VIT/Ccc1 proteins. Additionally, we identified a novel protein that may participate in iron uptake regulation, the overexpression of which leads to increased iron acquisition.